Ten novel MHC class II alleles identified in cynomolgus macaques of Vietnamese origin. (13th January 2016) - Wang, W.; He, D.‐D.; Mao, S.‐L.; Zhuo, M.; Ling, F.
Abstract : Five Mafa‐DPB1, two Mafa‐DQB1 and three Mafa‐DRB novel alleles are identified in Vietnamese cynomolgus macaques.